Housing finance markets in transition economies trends and challenges - Shinozaki, Shigehiro (Organisation for Economic Co-operation and Development, 2005)
Housing finance markets in Central and Eastern European countries are typically small in scale and under-developed, though it is generally recognized that fostering housing finance markets contributes to economic development and brings social benefits to the public. This book presents a comparative study on housing finance markets in the Central and Eastern European countries. It is based on an OECD market survey conducted in 2004 and on selected country data prepared for the OECD workshop on housing finance in transition economies held in December 2004. It reports on the progress and challenges in housing finance markets in Croatia, the Czech Republic, Estonia, Hungary, Kazakhstan, Lithuania, Latvia, Poland, Romania, the Slovak Republic, Slovenia and Ukraine.--Publisher's description.